Guru as an Academic Leader in Vedic Tradition: A Review - Neupane, Bharat; Gnawali, Laxman (Bodhi: An Interdisciplinary Journal, 2023)
Vedic literature from the Indian Subcontinent does not use the phrase ‘academic leadership’ or any other terminology precisely equivalent to this; still, rishi-munis , gurus, and even some kings with passion for knowledge, who provided the environment for exploration and dissemination of knowledge and wisdom can be considered as academic leaders in true sense. In this line, this article reports the review results on the concept of educational leadership depicted in Vedic literature. For this purpose, we explored writings on Vedic wisdom tradition and philosophy, mainly in Google Scholar, using the keyphrases “academic leadership in Vedic literature,” “education system in India,” “Sanatan philosophy,” “Hindu education system,” “Gurukul education,” and “education system in Mithila.” The review results revealed that academic leaders were selected based on practical expertise and specialization in content knowledge, particularly skills, knowledge, character, moral values, perseverance, and gratitude. Academic leaders were father figures, a source of inspiration, role models, and much more. Besides, leaders were characterized by honesty, devotion, and trust, and they had a passion for education and dedication to the profession with a desire for the quest for eternal truth. At current times, when the selection of leadership in academia is based on non-academic influence, such as political inclination, nepotism, and favoritism, neglecting leadership qualities and performance, particularly in Nepal and many other countries, the article provides valuable insights into academic leadership.